A new large green species of Litoria (Anura: Hylidae) from western New Guinea - Oliver, Paul; Richards, Stephen J.; Tjaturadi, Burhan; Iskandar, Djoko (Zootaxa, 2007)
A new species of large green treefrog of the genus Litoria is described from the Mamberamo Basin of western New Guinea. It can be distinguished from all congeners by a suite of characteristics including moderately large size (male SVL 56–68 mm), moderate finger webbing, labial stripe absent or very indistinct, and lateral body surfaces and webbing with distinctive light purple colouration. Morphologically, the new species is most similar to Litoria sanguinolenta and, to a lesser extent, L. infrafrenata. However, the advertisement call, a very long series of monotonously repeated, distinctly pulsed notes, differs from the calls of these two species.